2019
DOI: 10.1186/s12976-019-0102-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying heterogeneous contact patterns in Japan: a social contact survey

Abstract: Background Social contact surveys can greatly help in quantifying the heterogeneous patterns of infectious disease transmission. The present study aimed to conduct a contact survey in Japan, offering estimates of contact by age and location and validating a social contact matrix using a seroepidemiological dataset of influenza. Methods An internet-based questionnaire survey was conducted, covering all 47 prefectures in Japan and including a total of 1476 households. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 63 publications
9
33
0
Order By: Relevance
“…The scatter plot illustrating the distribution of children's age and that of their contacts showed that children came into contact with people of varying ages, suggesting that they can transmit diseases to a wide range of people. Consistent with previous studies [1,16,23], children may transmit an infection through contact with their peers and inter-generationally. Regarding the features of contact according to age, children aged 13~36 months showed more frequent contacts with their family members at home and had physical contacts lasting >4 hours with people they met daily, which is consistent with previous findings [11,24].…”
Section: Discussionsupporting
confidence: 90%
“…The scatter plot illustrating the distribution of children's age and that of their contacts showed that children came into contact with people of varying ages, suggesting that they can transmit diseases to a wide range of people. Consistent with previous studies [1,16,23], children may transmit an infection through contact with their peers and inter-generationally. Regarding the features of contact according to age, children aged 13~36 months showed more frequent contacts with their family members at home and had physical contacts lasting >4 hours with people they met daily, which is consistent with previous findings [11,24].…”
Section: Discussionsupporting
confidence: 90%
“…Approximately 50% of all contacts occurred at home, and this percentage was higher among infants and elderly people. The results showed a similar pattern to those seen in previous studies from many countries, i.e., that human contact patterns are highly age-dependent, with greater frequencies and some slight variations among the different regions of the country, which could in part be explained by cultural differences [10,[13][14][15][16].…”
Section: Introductionsupporting
confidence: 86%
“…There is evidence to suggest that social contacts should reduce when schools are closed. For example, it has been reported that students have contact with fewer people during weekends [3] and that the number of contacts children have with others approximately halves during the holidays [4,5]. Several studies have also examined illness transmission rates during planned school closures, reporting a reduction in illness during school holidays [6][7][8] and teacher strikes [9].…”
Section: Introductionmentioning
confidence: 99%